PENGEMBANGAN E-LKPD BERBASIS REACT MENGGUNAKAN WIZER.ME PADA POKOK BAHASAN TERMOKIMIA KELAS XI SMA/MA SEDERAJAT - Masayu, Risa Alia; Rasmiwetti, Rasmiwetti; Abdullah, Abdullah (Journal of Research and Education Chemistry, 2026)
This study aims to develop an E-LKPD (Digital Student Worksheet) based on the REACT model (Relating, Experiencing, Applying, Cooperating, Transferring) using Wizer.me for the topic of Thermochemistry in class XI SMA/MA (high school/equivalent). The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Validation was conducted by two content experts and one media expert, resulting in an average score of 94.41% for aspects of content validity, language, presentation, and graphics, as well as 93.18% for visual presentation and 100% for software utilization. Trials with teachers resulted in a score of 96.72%, while student responses obtained a score of 84.02%, both categorized as very good. These findings indicate that the developed E-LKPD is valid and effective in enhancing students' understanding of Thermochemistry concepts. This research also contributes to the development of innovative learning resources that support active and collaborative learning in the classroom.